Improving the science and evidence base of disaster response: a policy research study - Irene Anne Jillson; Michael Clarke; Claire Allen; Stephen Waller; Tracey Koehlmoos; William Mumford; Jeroen Jansen; Keith McKay; Alexandra Trant (BMC, 2019)
Abstract Background In order to elicit the knowledge, experience, and attitudes of individuals involved in disaster response with regard to evidence-based best practices, Evidence Aid and its institutional partners, Georgetown University and the Uniformed Services University of the Health Sciences, carried out a Policy Delphi study in 2015-2016. Methods Purposive and snowball methods were used to select study participants. The Delphi study comprised two rounds of iterative questions, with the questionnaires completed online. In addition, participants at the Evidence Aid conference in November 2016 discussed the findings in focus groups. Excel was used to analyze the quantitative data and Glaser and Strauss (1967) to analyze the qualitative data. Results Thirty-six participants responded to the first round of the study, 165 responded to the second round, and 30 participated in the focus group discussions. The salient findings include 1) ensuring that all key stakeholders are engaged in planning for and responding to disasters in a collaborative, coordinated manner-including local community members; 2) using, insofar as possible, evidence-based responses; 3) increasing and strengthening research to ensure that such data are available; and 4) addressing ethical, legal and social issues throughout the planning, immediate response, and post-disaster periods. Conclusions Recent humanitarian disasters, due to natural and man-made hazards or a combination of the two, reinforce the need for more effective, efficient, humane responses at the local, national and international levels. This study has yielded findings that can be used to strengthen planning and response by taking into account, where possible, evidence based on research that has been carried out with the engagement of community members and with support by key stakeholders. The most effective means of facilitating the development and implementation of consistent, coordinated policies and practices might be for the United Nations Office for Disaster Risk Reduction to take the lead in engaging key organizations in the required discussions and collaborations.